2008
DOI: 10.1097/aln.0b013e31816c89e1
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Photoplethysmogram in Circulatory Monitoring

Abstract: The photoplethysmogram is a noninvasive circulatory signal related to the pulsatile volume of blood in tissue and is displayed by many pulse oximeters and bedside monitors, along with the computed arterial oxygen saturation. The photoplethysmogram is similar in appearance to an arterial blood pressure waveform. Because the former is noninvasive and nearly ubiquitous in hospitals whereas the latter requires invasive measurement, the extraction of circulatory information from the photoplethysmogram has been a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
236
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(243 citation statements)
references
References 77 publications
1
236
0
6
Order By: Relevance
“…Similarly, the pulse oximeter trace can be an accurate indicator of the presence or absence of pulsatile flow distal to a cuff, so long as sufficient time is allowed when inflating ⁄ deflating the cuff [2]. Additional delay is added to the oximeter method by the processing of the oximetry signal, although the photoplethysmogram trace can also give information about the shape of the arterial waveform and the volaemic status of the patient [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the pulse oximeter trace can be an accurate indicator of the presence or absence of pulsatile flow distal to a cuff, so long as sufficient time is allowed when inflating ⁄ deflating the cuff [2]. Additional delay is added to the oximeter method by the processing of the oximetry signal, although the photoplethysmogram trace can also give information about the shape of the arterial waveform and the volaemic status of the patient [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…In such situations, the anaesthetist may rely on clinical signs of adequate end-organ perfusion such as the patient's colour and responsiveness, or may attempt to obtain an indication of the patient's BP by feeling for the radial arterial pulse or observing the pulse oximeter whilst the NIBP cuff inflates or deflates, the disappearance ⁄ return of a palpable pulsation or oximetry trace indicating systolic arterial pressure. Limited data have been published on the accuracy of these methods for estimating BP [1,2], and none that we are aware of in the obstetric setting or during regional anaesthesia. Our aim was therefore to study the usefulness of arterial palpation and pulse oximetry for estimating the NIBP machine-derived systolic pressure, in the context of obstetric regional anaesthesia.…”
mentioning
confidence: 99%
“…This cardiac-synchronous pulsatile component is assumed to depend solely on the arterial inflow of blood into a monitoring site such as the finger or earlobe [4]. As the ac PPG signal is similar in morphology to the arterial blood pressure waveform [5], it has been suggested that they are both influenced by similar vascular mechanisms [6]. Therefore, the PPG signal has been explored as a method to extract further circulatory and cardiovascular information from patients [1].…”
Section: Introductionmentioning
confidence: 99%
“…Less light is detected when a larger volume of blood is crossing the photodetector. Thus, the photodetector is able to detect the pulsatile flow in the arteries [45,46]. The HR can subsequently be calculated by an algorithm [44].…”
Section: Mobile Applicationsmentioning
confidence: 99%